The Influence of Brand Trust, Brand Familiarity, and Brand Experience on Brand Attachments - Dede Barijan; Endah Pri Ariningsih; Fitri Rahmawati (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
The development of technology in the automotive world today has progressed very rapidly. Thus, automotive companies must compete in winning market share in Indonesia. Business competition brings companies competing to produce products that consumers need and want. This study aims to determine the effect of brand trust on brand attachment, brand familiarity on brand attachment, and brand experience on brand attachment. Sampling using a purposive sampling technique. The data collection instrument used a questionnaire with a Likert scale. The questionnaire has been tested and has met the validity and reliability requirements. Data analysis was performed using multiple linear regression analysis. The results of data analysis show that brand trust has a positive effect on brand attachment, brand familiarity has a positive effect on brand attachment, and brand experience has a positive effect on brand attachment. Thus it can be concluded that brand trust, brand familiarity, and brand experience significantly influence brand attachment partially.